The Orphans' Nine Commandments - Holman, William Roger (Book collections on Project MUSE., 2007)
Roger Bechan was dropped off by his mother at the Society of the Friendless when he was six, where he began a long journey thorough 3 orphanages and several foster homes. This is his story.